ChemInform Abstract: Nucleophilic Nitration of Arynes by Sodium Nitrite and Its Multicomponent Reaction Leading to Double‐Functionalized Arenes. Issue 45 (October 2016) - Dhokale, Ranjeet A.; Mhaske, Santosh B.
Abstract: An unusual nucleophilic nitration of arynes, generated by Kobayashi′s method, is studied.